Proceedings of a Workshop on Deterring Cyberattacks: Informing Strategies and Developing Options for U.S. Policy - National Research Council (The National Academies Press, 2010)
In a world of increasing dependence on information technology, the prevention of cyberattacks on a nation's important computer and communications systems and networks is a problem that looms large. Given the demonstrated limitations of passive cybersecurity defense measures, it is natural to consider the possibility that deterrence might play a useful role in preventing cyberattacks against the United States and its vital interests. At the request of the Office of the Director of National Intelligence, the National Research Council undertook a two-phase project aimed to foster a broad, multidisciplinary examination of strategies for deterring cyberattacks on the United States and of the possible utility of these strategies for the U.S. government. The first phase produced a letter report providing basic information needed to understand the nature of the problem and to articulate important questions that can drive research regarding ways of more effectively preventing, discouraging, and inhibiting hostile activity against important U.S. information systems and networks. The second phase of the project entailed selecting appropriate experts to write papers on questions raised in the letter report. A number of experts, identified by the committee, were commissioned to write these papers under contract with the National Academy of Sciences. Commissioned papers were discussed at a public workshop held June 10-11, 2010, in Washington, D.C., and authors revised their papers after the workshop. Although the authors were selected and the papers reviewed and discussed by the committee, the individually authored papers do not reflect consensus views of the committee, and the reader should view these papers as offering points of departure that can stimulate further work on the topics discussed. The papers presented in this volume are published essentially as received from the authors, with some proofreading corrections made as limited time allowed.
Keywords: Conflict and Security Issues; Computers and Information Technology

Guidebook on Best Practices for Airport Cybersecurity - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s Airport Cooperative Research Program (ACRP) Report 140: Guidebook on Best Practices for Airport Cybersecurity provides information designed to help reduce or mitigate inherent risks of cyberattacks on technology-based systems.Traditional IT infrastructure such as servers, desktops, and network devices are covered along with increasingly sophisticated and interconnected industrial control systems, such as baggage handling, temperature control, and airfield lighting systems.The guidebook also includes a CD-ROM of multimedia material that may be used to educate all staff at airports about the need, and how, to be diligent against cybersecurity threats.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Professionalizing the Nation's Cybersecurity Workforce?: Criteria for Decision-Making - National Research Council (The National Academies Press, 2013)
Professionalizing the Nation's Cybersecurity Workforce? Criteria for Decision-Making considers approaches to increasing the professionalization of the nation's cybersecurity workforce. This report examines workforce requirements for cybersecurity and the segments and job functions in which professionalization is most needed; the role of assessment tools, certification, licensing, and other means for assessing and enhancing professionalization; and emerging approaches, such as performance-based measures. It also examines requirements for the federal (military and civilian) workforce, the private sector, and state and local government. The report focuses on three essential elements: (1) understanding the context for cybersecurity workforce development, (2) considering the relative advantages, disadvantages, and approaches to professionalizing the nation's cybersecurity workforce, and (3) setting forth criteria that can be used to identify which, if any, specialty areas may require professionalization and set forth criteria for evaluating different approaches and tools for professionalization. Professionalizing the Nation's Cybersecurity Workforce? Criteria for Decision-Making characterizes the current landscape for cybersecurity workforce development and sets forth criteria that the federal agencies participating in the National Initiative for Cybersecurity Education—as well as organizations that employ cybersecurity workers—could use to identify which specialty areas may require professionalization and to evaluate different approaches and tools for professionalization.
Keywords: Computers and Information Technology; Education; Industry and Labor

Making the Nation Safer: The Role of Science and Technology in Countering Terrorism - National Research Council (The National Academies Press, 2002)
Vulnerabilities abound in U.S. society. The openness and efficiency of our key infrastructures — transportation, information and telecommunications systems, health systems, the electric power grid, emergency response units, food and water supplies, and others — make them susceptible to terrorist attacks. Making the Nation Safer discusses technical approaches to mitigating these vulnerabilities. A broad range of topics are covered in this book, including: Nuclear and radiological threats, such as improvised nuclear devices and "dirty bombs;" Bioterrorism, medical research, agricultural systems and public health; Toxic chemicals and explosive materials; Information technology, such as communications systems, data management, cyber attacks, and identification and authentication systems; Energy systems, such as the electrical power grid and oil and natural gas systems; Transportation systems; Cities and fixed infrastructures, such as buildings, emergency operations centers, and tunnels; The response of people to terrorism, such as how quality of life and morale of the population can be a target of terrorists and how people respond to terrorist attacks; and Linked infrastructures, i.e. the vulnerabilities that result from the interdependencies of key systems. In each of these areas, there are recommendations on how to immediately apply existing knowledge and technology to make the nation safer and on starting research and development programs that could produce innovations that will strengthen key systems and protect us against future threats. The book also discusses issues affecting the government's ability to carry out the necessary science and engineering programs and the important role of industry, universities, and states, counties, and cities in homeland security efforts. A long term commitment to homeland security is necessary to make the nation safer, and this book lays out a roadmap of how science and engineering can assist in countering terrorism.
Keywords: Conflict and Security Issues

Biometric Recognition: Challenges and Opportunities - National Research Council (The National Academies Press, 2010)
Biometric recognition--the automated recognition of individuals based on their behavioral and biological characteristic--is promoted as a way to help identify terrorists, provide better control of access to physical facilities and financial accounts, and increase the efficiency of access to services and their utilization. Biometric recognition has been applied to identification of criminals, patient tracking in medical informatics, and the personalization of social services, among other things. In spite of substantial effort, however, there remain unresolved questions about the effectiveness and management of systems for biometric recognition, as well as the appropriateness and societal impact of their use. Moreover, the general public has been exposed to biometrics largely as high-technology gadgets in spy thrillers or as fear-instilling instruments of state or corporate surveillance in speculative fiction. Now, as biometric technologies appear poised for broader use, increased concerns about national security and the tracking of individuals as they cross borders have caused passports, visas, and border-crossing records to be linked to biometric data. A focus on fighting insurgencies and terrorism has led to the military deployment of biometric tools to enable recognition of individuals as friend or foe. Commercially, finger-imaging sensors, whose cost and physical size have been reduced, now appear on many laptop personal computers, handheld devices, mobile phones, and other consumer devices. Biometric Recognition: Challenges and Opportunities addresses the issues surrounding broader implementation of this technology, making two main points: first, biometric recognition systems are incredibly complex, and need to be addressed as such. Second, biometric recognition is an inherently probabilistic endeavor. Consequently, even when the technology and the system in which it is embedded are behaving as designed, there is inevitable uncertainty and risk of error. This book elaborates on these themes in detail to provide policy makers, developers, and researchers a comprehensive assessment of biometric recognition that examines current capabilities, future possibilities, and the role of government in technology and system development.
Keywords: Computers and Information Technology; Engineering and Technology; Conflict and Security Issues

A 21st Century Cyber-Physical Systems Education - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Cyber-physical systems (CPS) are "engineered systems that are built from, and depend upon, the seamless integration of computational algorithms and physical components." CPS can be small and closed, such as an artificial pancreas, or very large, complex, and interconnected, such as a regional energy grid. CPS engineering focuses on managing inter- dependencies and impact of physical aspects on cyber aspects, and vice versa. With the development of low-cost sensing, powerful embedded system hardware, and widely deployed communication networks, the reliance on CPS for system functionality has dramatically increased. These technical developments in combination with the creation of a workforce skilled in engineering CPS will allow the deployment of increasingly capable, adaptable, and trustworthy systems. Engineers responsible for developing CPS but lacking the appropriate education or training may not fully understand at an appropriate depth, on the one hand, the technical issues associated with the CPS software and hardware or, on the other hand, techniques for physical system modeling, energy and power, actuation, signal processing, and control. In addition, these engineers may be designing and implementing life-critical systems without appropriate formal training in CPS methods needed for verification and to assure safety, reliability, and security. A workforce with the appropriate education, training, and skills will be better positioned to create and manage the next generation of CPS solutions. A 21st Century Cyber-Physical Systems Education examines the intellectual content of the emerging field of CPS and its implications for engineering and computer science education. This report is intended to inform those who might support efforts to develop curricula and materials; faculty and university administrators; industries with needs for CPS workers; and current and potential students about intellectual foundations, workforce requirements, employment opportunities, and curricular needs.
Keywords: Computers and Information Technology

Securing the Vote: Protecting American Democracy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
During the 2016 presidential election, America's election infrastructure was targeted by actors sponsored by the Russian government. Securing the Vote: Protecting American Democracy examines the challenges arising out of the 2016 federal election, assesses current technology and standards for voting, and recommends steps that the federal government, state and local governments, election administrators, and vendors of voting technology should take to improve the security of election infrastructure. In doing so, the report provides a vision of voting that is more secure, accessible, reliable, and verifiable.
Keywords: Behavioral and Social Sciences

Looking Ahead at the Cybersecurity Workforce at the Federal Aviation Administration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Federal Aviation Administration (FAA) has overseen significant upgrades to the technology used to manage aviation operations to increase the safety and efficiency of the National Airspace System (NAS). Though necessary to regular operations, these modern computing and communications systems provide a greater attack surface for criminals, terrorists, or nation-states to exploit and thereby increase the potential for cybersecurity threats to the NAS and its constituents. The future safety and security of air travel will rely in part on the ability of the FAA to build a workforce capable of addressing the evolving cybersecurity threat landscape. Securing the computers, networks, and data that underpin modern aviation depends in part on the FAA having enough cybersecurity professionals (capacity) with the right knowledge, skills, and abilities (capability)). It also depends on the FAA's workforce having sufficient diversity of backgrounds and experience. Such diversity is critical in analyzing cybersecurity problems and widely understood to be a "functional imperative" for effective cybersecurity programs. At the request of Congress, the publication examines the FAA's cybersecurity workforce challenges, reviews the current strategy for meeting those challenges, and recommends ways to strengthen the FAA's cybersecurity workforce.
Keywords: Industry and Labor; Computers and Information Technology

Toward a Safer and More Secure Cyberspace - National Research Council; National Academy of Engineering (The National Academies Press, 2007)
Given the growing importance of cyberspace to nearly all aspects of national life, a secure cyberspace is vitally important to the nation, but cyberspace is far from secure today. The United States faces the real risk that adversaries will exploit vulnerabilities in the nation’s critical information systems, thereby causing considerable suffering and damage. Online e-commerce business, government agency files, and identity records are all potential security targets. Toward a Safer and More Secure Cyberspace examines these Internet security vulnerabilities and offers a strategy for future research aimed at countering cyber attacks. It also explores the nature of online threats and some of the reasons why past research for improving cybersecurity has had less impact than anticipated, and considers the human resource base needed to advance the cybersecurity research agenda. This book will be an invaluable resource for Internet security professionals, information technologists, policy makers, data stewards, e-commerce providers, consumer protection advocates, and others interested in digital security and safety.
Keywords: Computers and Information Technology; Conflict and Security Issues

Update of Security 101: A Physical Security and Cybersecurity Primer for Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Since 2009, when NCHRP's last Security 101 report was released, there have been significant advances in transportation security approaches, including new strategies, programs, and ways of doing business that have increased the security of transportation systems as well as ensured their resiliency.Hazards and threats to the system have also continued to evolve since 2009. While the incidence of large-scale terrorist attacks has remained small, transportation agencies are at increasingly greater risk from system-disrupting events due to natural causes, unintentional human intervention, and intentional criminal acts, such as active-shooter incidents. Cyber risks also are increasing and can impact not only data, but the control systems—like tunnel-ventilation systems—operated by transportation agencies.>The TRB National Cooperative Highway Research Program's NCHRP Research Report 930: Update of Security 101: A Physical Security and Cybersecurity Primer for Transportation Agencies provides valuable information about current and accepted practices associated with both physical and cyber security and its applicability to surface transportation.The report is accompanied by a PowerPoint for the project and NCHRP Web-Only Document 266: Developing a Physical and Cyber Security Primer for Transportation Agencies.
Keywords: Transportation and Infrastructure

Improving State Voter Registration Databases: Final Report - National Research Council (The National Academies Press, 2010)
Improving State Voter Registration Databases outlines several actions that are needed to help make voter registration databases capable of sharing information within state agencies and across state lines. These include short-term changes to improve education, dissemination of information, and administrative processes, and long-term changes to make improvements in data collection and entry, matching procedures, and ensure privacy and security.
Keywords: Policy for Science and Technology; Industry and Labor; Behavioral and Social Sciences

Protection of Transportation Infrastructure from Cyber Attacks: A Primer - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Protection of Transportation Infrastructure from Cyber Attacks: A Primer provides transportation organizations with reference materials concerning cybersecurity concepts, guidelines, definitions, and standards. The primer is a joint product of two TRB Cooperative Research Programs, and is categorized as Transit Cooperative Research Program (TCRP) Web-Only Document 67 and National Cooperative Highway Research Program (NCHRP) Web-Only Document 221.The Primer delivers strategic, management, and planning information associated with cybersecurity and its applicability to transit and state DOT operations. It includes definitions and rationales that describe the principles and practices that enable effective cybersecurity risk management. The primer provides transportation managers and employees with greater context and information regarding the principles of information technology and operations systems security planning and procedures.The report is supplemented with an Executive Briefing for use as a 20-minute presentation to senior executives on security practices for transit and DOT cyber and industrial control systems. A PowerPoint summary of the project is also available.
Keywords: Transportation and Infrastructure

Protection of Transportation Infrastructure from Cyber Attacks: A Primer - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Protection of Transportation Infrastructure from Cyber Attacks: A Primer provides transportation organizations with reference materials concerning cybersecurity concepts, guidelines, definitions, and standards. The primer is a joint product of two TRB Cooperative Research Programs, and is categorized as Transit Cooperative Research Program (TCRP) Web-Only Document 67 and National Cooperative Highway Research Program (NCHRP) Web-Only Document 221.The Primer delivers strategic, management, and planning information associated with cybersecurity and its applicability to transit and state DOT operations. It includes definitions and rationales that describe the principles and practices that enable effective cybersecurity risk management. The primer provides transportation managers and employees with greater context and information regarding the principles of information technology and operations systems security planning and procedures.The report is supplemented with an Executive Briefing for use as a 20-minute presentation to senior executives on security practices for transit and DOT cyber and industrial control systems. A PowerPoint summary of the project is also available.
Keywords: Transportation and Infrastructure

Software for Dependable Systems: Sufficient Evidence? - National Research Council (The National Academies Press, 2007)
The focus of Software for Dependable Systems is a set of fundamental principles that underlie software system dependability and that suggest a different approach to the development and assessment of dependable software. Unfortunately, it is difficult to assess the dependability of software. The field of software engineering suffers from a pervasive lack of evidence about the incidence and severity of software failures; about the dependability of existing software systems; about the efficacy of existing and proposed development methods; about the benefits of certification schemes; and so on. There are many anecdotal reports, which—although often useful for indicating areas of concern or highlighting promising avenues of research—do little to establish a sound and complete basis for making policy decisions regarding dependability. The committee regards claims of extraordinary dependability that are sometimes made on this basis for the most critical of systems as unsubstantiated, and perhaps irresponsible. This difficulty regarding the lack of evidence for system dependability leads to two conclusions: (1) that better evidence is needed, so that approaches aimed at improving the dependability of software can be objectively assessed, and (2) that, for now, the pursuit of dependability in software systems should focus on the construction and evaluation of evidence. The committee also recognized the importance of adopting the practices that are already known and used by the best developers; this report gives a sample of such practices. Some of these (such as systematic configuration management and automated regression testing) are relatively easy to adopt; others (such as constructing hazard analyses and threat models, exploiting formal notations when appropriate, and applying static analysis to code) will require new training for many developers. However valuable, though, these practices are in themselves no silver bullet, and new techniques and methods will be required in order to build future software systems to the level of dependability that will be required.
Keywords: Computers and Information Technology

Decrypting the Encryption Debate: A Framework for Decision Makers - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Encryption protects information stored on smartphones, laptops, and other devices - in some cases by default. Encrypted communications are provided by widely used computing devices and services - such as smartphones, laptops, and messaging applications - that are used by hundreds of millions of users. Individuals, organizations, and governments rely on encryption to counter threats from a wide range of actors, including unsophisticated and sophisticated criminals, foreign intelligence agencies, and repressive governments. Encryption on its own does not solve the challenge of providing effective security for data and systems, but it is an important tool. At the same time, encryption is relied on by criminals to avoid investigation and prosecution, including criminals who may unknowingly benefit from default settings as well as those who deliberately use encryption. Thus, encryption complicates law enforcement and intelligence investigations. When communications are encrypted "end-to-end," intercepted messages cannot be understood. When a smartphone is locked and encrypted, the contents cannot be read if the phone is seized by investigators. Decrypting the Encryption Debate reviews how encryption is used, including its applications to cybersecurity; its role in protecting privacy and civil liberties; the needs of law enforcement and the intelligence community for information; technical and policy options for accessing plaintext; and the international landscape. This book describes the context in which decisions about providing authorized government agencies access to the plaintext version of encrypted information would be made and identifies and characterizes possible mechanisms and alternative means of obtaining information.
Keywords: Computers and Information Technology

Cybersecurity of Freight Information Systems: A Scoping Study -- Special Report 274 - Transportation Research Board; National Research Council (The National Academies Press, 2003)
TRB Special Report 274 - Cybersecurity of Freight Information Systems: A Scoping Study reviews trends in the use of information technology in the freight transportation industry and assesses potential vulnerabilities to a cyberattack. Special Report 274 Summary
Keywords: Transportation and Infrastructure; Computers and Information Technology

Software Update as a Mechanism for Resilience and Security: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Software update is an important mechanism by which security changes and improvements are made in software, and this seemingly simple concept encompasses a wide variety of practices, mechanisms, policies, and technologies. To explore the landscape further, the Forum on Cyber Resilience hosted a workshop featuring invited speakers from government, the private sector, and academia. This publication summarizes the presentations and discussions from the workshop.
Keywords: Computers and Information Technology

Asking the Right Questions About Electronic Voting - National Research Council (The National Academies Press, 2006)
Many election officials look to electronic voting systems as a means for improving their ability to more effectively conduct and administer elections. At the same time, many information technologists and activists have raised important concerns regarding the security of such systems. Policy makers are caught in the midst of a controversy with both political and technological overtones. The public debate about electronic voting is characterized by a great deal of emotion and rhetoric. Asking the Right Questions About Electronic Voting describes the important questions and issues that election officials, policy makers, and informed citizens should ask about the use of computers and information technology in the electoral process—focusing the debate on technical and policy issues that need resolving. The report finds that while electronic voting systems have improved, federal and state governments have not made the commitment necessary for e-voting to be widely used in future elections. More funding, research, and public education are required if e-voting is to become viable.
Keywords: Industry and Labor; Behavioral and Social Sciences

Foundational Cybersecurity Research: Improving Science, Engineering, and Institutions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Attaining meaningful cybersecurity presents a broad societal challenge. Its complexity and the range of systems and sectors in which it is needed mean that successful approaches are necessarily multifaceted. Moreover, cybersecurity is a dynamic process involving human attackers who continue to adapt. Despite considerable investments of resources and intellect, cybersecurity continues to poses serious challenges to national security, business performance, and public well-being. Modern developments in computation, storage and connectivity to the Internet have brought into even sharper focus the need for a better understanding of the overall security of the systems we depend on. Foundational Cybersecurity Research focuses on foundational research strategies for organizing people, technologies, and governance. These strategies seek to ensure the sustained support needed to create an agile, effective research community, with collaborative links across disciplines and between research and practice. This report is aimed primarily at the cybersecurity research community, but takes a broad view that efforts to improve foundational cybersecurity research will need to include many disciplines working together to achieve common goals.
Keywords: Computers and Information Technology; Conflict and Security Issues

Who Goes There?: Authentication Through the Lens of Privacy - National Research Council (The National Academies Press, 2003)
Who Goes There?: Authentication Through the Lens of Privacy explores authentication technologies (passwords, PKI, biometrics, etc.) and their implications for the privacy of the individuals being authenticated. As authentication becomes ever more ubiquitous, understanding its interplay with privacy is vital. The report examines numerous concepts, including authentication, authorization, identification, privacy, and security. It provides a framework to guide thinking about these issues when deciding whether and how to use authentication in a particular context. The book explains how privacy is affected by system design decisions. It also describes government’s unique role in authentication and what this means for how government can use authentication with minimal invasions of privacy. In addition, Who Goes There? outlines usability and security considerations and provides a primer on privacy law and policy.
Keywords: Computers and Information Technology